Influence of Heat Treatment on Microstructure and Properties of NiTi46 Alloy Consolidated by Spark Plasma Sintering - Salvetr, Pavel; Dlouhý, Jaromír; Školáková, Andrea; Průša, Filip; Novák, Pavel; Karlík, Miroslav; Haušild, Petr (Materials (Basel, Switzerland), 2019)
Ni-Ti alloys are considered to be very important shape memory alloys with a wide application area including, e.g., biomaterials, actuators, couplings, and components in automotive, aerospace, and robotics industries. In this study, the NiTi46 (wt.%) alloy was prepared by a combination of self-propagating high-temperature synthesis, milling, and spark plasma sintering consolidation at three various temperatures. The compacted samples were subsequently heat-treated at temperatures between 400 °C and 900 °C with the following quenching in water or slow cooling in a closed furnace. The influence of the consolidation temperature and regime of heat treatment on the microstructure, mechanical properties, and temperatures of phase transformation was evaluated. The results demonstrate the brittle behaviour of the samples directly after spark plasma sintering at all temperatures by the compressive test and no transformation temperatures at differential scanning calorimetry curves. The biggest improvement of mechanical properties, which was mainly a ductility enhancement, was achieved by heat treatment at 700 °C. Slow cooling has to be recommended in order to obtain the shape memory properties.
Keywords: hardness; compressive test; self-propagating high-temperature synthesis; shape memory; spark plasma sintering; aging; Ni-Ti alloy